Running Subcuticular Sutures Versus Simple Interrupted Suture in Wound Healing of Fibroadenoma Patients: A Randomised Control Trial - Dhirendra Nath Choudhury; Bibhu Priyo Das; Bibhu Priyo Das; Eeshan Chakraborty (National Board of Examinations Journal of Medical Sciences, 2025)
Objectives: To compare wound healing in post-operative patients of fibroadenoma when skin closure is done with running subcuticular suture as compared to simple interrupted suture. Methods: This was a prospective, randomized controlled clinical trial conducted in a hospital setting. Here, the scar quality, patient comfort, time taken for wound closure and postoperative complications were compared when the incision was closed with running subcuticular suture as compared to simple interrupted suture. Data was collected on postoperative day 7 when the patient came for stitch removal using the VAS (Visual Analogue Scale) and Modified HWES (Hollander Wound Evaluation Scale) scoring systems. The data were collected and analysed by using the statistical software ‘R’. The key outcome measures included VAS scores, HWES, and time. Results: This study included a total of 60 patients. Out of the these, 54 met the inclusion and exclusion criteria, while the remaining patients were lost in follow-up. 24 were enrolled into group A (Running Subcuticular) and 30 in group B (Simple Interrupted). The mean VAS score for Scar quality (as given by the patients) for Group A was 9.6667 and 9.1 for Group B. The mean VAS score for patient comfort was 0.125 for Group A and 0.5 for Group B. The mean HWES score for Group A was 0.66667 and for Group B was 0.73333. The mean closure time was 5.2083 minutes for Group A and 2.7333 minutes for Group B. 2 cases (8.333%) of wound dehiscence following superficial wound infection were observed in Group A and 1 case (3.333%) in Group B. Conclusion: The cosmetic outcome showed better results with running subcuticular sutures as compared to simple interrupted sutures. Patient comfort was more postoperatively with running subcuticular sutures. However, simple interrupted sutures appear to be more time saving. No comment could be satisfactorily made on the postoperative complications as the sample size was too small in this study.